Persepsi Mahasiswa Terhadap Budaya FOMO Gen Z di D.I. Yogyakarta - Sidiq tri hendriyanto; Octavianus Putra Pratama; Andrean Pratama; Waltrudis Alethio (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study explores how Generation Z students in the Special Region of Yogyakarta perceive the Fear of Missing Out (FOMO) phenomenon and how it affects their social interactions and psychological well-being. Utilizing a qualitative approach with a phenomenological method, the data were gathered through in-depth interviews with five students from different districts. The results indicate that social media plays a crucial role in intensifying FOMO, which manifests through constant trend-following, self-comparison, and decisions driven by external pressure rather than personal intention. This leads to emotional issues such as anxiety, stress, and mental fatigue. Nonetheless, some respondents have begun to recognize the need for self-regulation and mindful use of social media. In this context, FOMO is shaped by personal perception, social influence, and a lack of intrinsic motivation. Strengthening digital awareness and self-management skills are therefore essential in addressing the impact of FOMO among students.